2020
DOI: 10.1002/jcp.29887
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel alternative splicing of bovine lncRNA lncFAM200B and its effects on preadipocyte proliferation

Abstract: Adipogenesis is closely related to human health, livestock growth, and meat quality. A previous study identified that bovine lncFAM200B promoter has high activity in 3T3-L1 mice preadipocytes. Thus, lncFAM200B was a candidate gene for regulating adipogenesis. This study aimed to uncover the role of lncFAM200B in bovine adipogenesis and identify novel genetic variations within the bovine lncFAM200B gene. An expression analysis found that lncFAM200B was expressed higher in fat than that in muscle, but the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Furthermore, we identi ed important interactions between certain lncRNAs and mRNAs that could mediate host immune response at the post-transcriptional level. lncRNAs are becoming known to be involved in several biogenetic processes that may regulate disease pathogenesis 14,44 . We hypothesized that lncRNAs that bind to multiple mRNA target sequences could serve as drug targets and have the potential to modify or regulate immune signaling pathways, ameliorating the over-or under-production of cytokines or chemokine during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identi ed important interactions between certain lncRNAs and mRNAs that could mediate host immune response at the post-transcriptional level. lncRNAs are becoming known to be involved in several biogenetic processes that may regulate disease pathogenesis 14,44 . We hypothesized that lncRNAs that bind to multiple mRNA target sequences could serve as drug targets and have the potential to modify or regulate immune signaling pathways, ameliorating the over-or under-production of cytokines or chemokine during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have underlined the significance of ncRNAs in adipogenesis, especially in regulating the proliferation and differentiation of adipocytes. 10 , 11 , 12 , 13 The expression of ncRNAs is specific to cells and tissues and may differ between various stages of differentiation. This observation suggests that ncRNAs may be fine-tuning factors of cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…In livestock production, a novel lncRNA mainly localized to the nucleus and named miR-221 host gene (MIR221HG) because it overlaps with miR-221 in the genome was proven to regulate bovine adipocyte differentiation [69]. Studies found that the expression of lnc FAM200B in bovines had a significant positive correlation with C/EBPα expression, suggesting that lnc FAM200B might participate in the regulation of adipocyte development [70]. In addition, evidence indicated that PSXV-9, a novel antisense lncRNA of C/EBPα, could inhibit bovine adipogenic differentiation [71].…”
Section: A C C E P T E Dmentioning
confidence: 99%